2015
DOI: 10.1248/bpb.b15-00527
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation Induced by Atrial Natriuretic Peptide Is Impaired in Carotid but Not Renal Arteries from Spontaneously Hypertensive Rats Due to Reduced BK<sub>Ca</sub> Channel Activity

Abstract: Atrial natriuretic peptide (ANP) plays an important role in vascular functions such as blood pressure regulation and relaxant activity. Individual vascular beds exhibit differences in vascular reactivity to various ligands, however, the difference in responsiveness to ANP between carotid and renal arteries and the molecular mechanisms of its vasorelaxant activity in a pathophysiological state, including hypertension, remain unclear. We therefore investigated this issue by exposing carotid and renal artery ring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…In the present study, we hypothesized that hyper-reactivity to 5-HT in carotid arteries was observed in hypertension through activations of these kinases. To test this hypothesis, we used carotid arteries isolated from spontaneously hypertensive rats (SHR), which is a widely used experimental genetic hypertensive model [18,31,35,37,52,56].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we hypothesized that hyper-reactivity to 5-HT in carotid arteries was observed in hypertension through activations of these kinases. To test this hypothesis, we used carotid arteries isolated from spontaneously hypertensive rats (SHR), which is a widely used experimental genetic hypertensive model [18,31,35,37,52,56].…”
Section: Introductionmentioning
confidence: 99%
“…Following incubation under these three conditions at 37掳C for 23 卤 1 h, vascular function was assessed by our previously-established organ bath technique. [26][27][28]30,32,[36][37][38] Subsequently, the rings were mounted into the organ bath system. After stabilization, the rings were exposed to an 80 mM high-K + solution and washed with modified Krebs-Henseleit solution [KHS; comprising (in mM) 118.0 NaCl, 4.7 KCl, 25.0 NaHCO 3 , 1.8 CaCl 2 , 1.2 NaH 2 PO 4 , 1.2 MgSO 4 , and 11.0 glucose].…”
Section: Methodsmentioning
confidence: 99%
“…The systolic blood pressure (SBP) of 13-or 14-week-old rats was measured, as previously described. 22,25) In brief, SBP was measured employing the tail-cuff method using a blood pressure analyzer (BP-98A; Softron, Tokyo, Japan) after the rat had been in a constant-temperature box at 37掳C for at least 5 min. Surgical procedures were performed under anesthetic cover of isoflurane as previously described.…”
Section: 18)mentioning
confidence: 99%
“…22,25,[32][33][34] Functional Studies Vascular isometric force was essentially recorded as described in our previous studies. 13,17,22,25,26,28,[32][33][34] Concentration-response curves to ATP (10 for 20 min prior to PE application. To investigate the effect of endothelium on relaxations, we analyzed concentrationresponse curves in the presence/absence of endothelium of superior mesenteric arteries from Wistar rat at 17 weeks of age.…”
Section: 18)mentioning
confidence: 99%
See 1 more Smart Citation